(untitled) (The Strategic Review for Southern Africa, 2020)
The demise of colonial-apartheid created a heightened sense of euphoria that was accompanied by great expectations in South Africa. Inevitably, the broad spectrum of South Africans expected the new dispensation to birth a fertile social, political and economic ground for national unity and reconciliation and social cohesion through a just and equitable democratic society. In thisregard, various institutional frameworks were transformed to be in sync with the new requirements placed on a democratising society. Historically, racial social engineering had profoundly fractured the South African society and made it difficult for society to cohere. Among these transformed institutional frameworks was the legislature, which is one of three arms of government that works in conjunction with the executive and judicial branches. At the core of the legislative branch is legislation (creating or amending new laws), oversight (control over the executive and custodian of natural resources) and deliberation (representative between the people and government). In this article, we contend that given the centrality of the legislature in driving the direction of the country, this institution has betrayed the hopes, aspirations and sensibilities of South Africans by being ineffective and irresponsible in its functions. Methodologically, the paper uses desktop research, and draws from primary and secondary documentary evidence. Structurally, it covers the following: the role of the legislature during colonialapartheid; the new dispensation and the new role of the legislature; and the challenges faced by the legislature under new determinant conditions. The article reaches the conclusion that the failure of South Africa to transform into a just and cohesive non-racial, non-sexist society is, to a great extent, a function of the dismal performance of the legislature. Therefore, pursuant on the re-imagination of South Africa from its colonial-apartheid past, the legislature will have to perform its roles and functions effectively and take its responsibilities seriously in order to ensure social cohesion through inclusive development.